Sensitivity of pre-budded seedlings and sugar cane multibud setts to pre-emergent herbicides - Silva, Paulo Vinicius da; Milagres Viana, Henrique Rodrigues; Malardo, Marcelo Rafael; Dias, Roque de Carvalho [UNESP]; Inacio, Estela Maris; Ribeiro, Nagila Moraes [UNESP]; Monquero, Patricia Andrea; Christoffoleti, Pedro Jacob (Univ Federal Mato Grosso, 2020)
The sugarcane, grown through pre-budded seedlings and multibud setts, may have more sensitive to herbicides compared to conventional. The objective of this study was to evaluate the initial selectivity of pre-emergent herbicide treatment in sugarcane varieties cultivated in the pre-budded seedlings and multibud setts systems. Two experiments were carried out in the greenhouse, one with MPBs (RB966928 and IAC 5000) and the other with multibud setts (RB92579 and RB966928). The design was completely randomized, with four replications in an 8 x 5 factorial scheme, with eight treatments: amicarbazone (1400 g ha(-1)); metribuzin (1920 g ha(-1)); indaziflam (100 g ha(-1)); isoxaflutole (105 g ha(-1)); amicarbazone + indaziflam (1005 + 75 g ha(-1)); metribuzin + indaziflam (960 + 75 g ha(-1)), isoxaflutole + indaziflam (75 + 75 g ha(-1)) and control (without herbicides) and five evaluation periods (7, 14, 21, 28 and 35 days after application of the DAT and emergency treatments, for MPBs and multibud setts, respectively). In MPBs, the herbicides amicarbazone and metribuzin, resulted in 0.00% phytotoxicity in both varieties. In multibud setts, isoxaflutole alone and associated with indaziflam resulted in high phytotoxicity regardless of variety. Soon the planting system and the varieties, influence the selectivity of herbicides in the culture of sugarcane.
Keywords: sugarcane-plant; phytotoxicity; application; planting systems